Agenda for caring - Rao, Vidya (Mussoorie, 1996)
This book how caring's applicability cuts across cultural and geographic borders. "A Global Agenda for Caring" is a significant contribution to t he world's body of research on caring, and it brings us closer to realizing the full potential of studying caring worldwide.
Keywords: Health care